What is important ? = Kas ir svarigi ? - Krese, Solvita; Tifentale, Alise (Riga : Latvian Centre for Contemporary Art Riga, 2004)
Apse, Inese ; Balcus, Arnis ; Balode, Gunda ; Bankovska, Anda ; Bley, Aija ; Drazniece, Liene ; Epners, Kristaps ; Grauds, Martins ; Gravlejs, Ivars ; Gruzna, Evija ; Gulbe, Liga ; Halilova, Laila ; Jerohina, Ieva ; Laurenovica, Liga ; Lihaceva, Elina ; Podnieks, Kaspars ; Salmanis, Kriss ; Stakle, Alnis ; Tifentale, Alise ; Virina, Ieva
biog. per kunstenaar
Lets
Engels
Exhibition. What is important ? = Kas ir svarigi ?. Latvian Centre for Contemporary Art Riga. 14.05.2004 - 13.06.2004
boek